Bone Marrow-Derived Multipotent Stromal Cells Attenuate Inflammation in Obliterative Airway Disease in Mouse Tracheal Allografts. (10th September 2014) - Casey, Alicia; Dirks, Fabian; Liang, Olin D.; Harrach, Hakima; Schuette-Nuetgen, Katharina; Leeman, Kristen; Kim, Carla F.; Gerard, Craig; Subramaniam, Meera
Abstract : Obliterative bronchiolitis (OB) remains the most significant cause of death in long-term survival of lung transplantation. Using an established murine heterotopic tracheal allograft model, the effects of different routes of administration of bone marrow-derived multipotent stromal cells (MSCs) on the development of OB were evaluated. Tracheas from BALB/c mice were implanted into the subcutaneous tissue of major histocompatibility complex- (MHC-) disparate C57BL/6 mice. At the time of transplant, bone marrow-derived MSCs were administered either systemically or locally or via a combination of the two routes. The allografts were explanted at various time points after transplantation and were evaluated for epithelial integrity, inflammatory cell infiltration, fibrosis, and luminal obliteration. We found that the most effective route of bone marrow-derived MSC administration is the combination of systemic and local delivery. Treatment of recipient mice with MSCs suppressed neutrophil, macrophage, and T-cell infiltration and reduced fibrosis. These beneficial effects were observed despite lack of significant MSC epithelial engraftment or new epithelial cell generation. Our study suggests that optimal combination of systemic and local delivery of MSCs may ameliorate the development of obliterative airway disease through modulation of immune response.